2020
DOI: 10.1088/2053-1591/ab6e31
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grading tungsten powders on properties of CuW alloy

Abstract: Considering the advantages and disadvantages of CuW alloys with different single particle size of tungsten powder, CuW alloys with three kinds of tungsten powders: ultramicron (50 μm), micron (6-8 μm), submicron(0.4 μm) were prepared by the infiltration method. Microstructure of the CuW alloy with different grading ration of tungsten powder were characterized via field-emission scanning electron microscope (SEM). The Vacuum electrical breakdown properties were studied by electrical breakdown test. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Existing processes for the preparation of copper-based contact materials include: induced copper powder fusion infiltration, pre-sintered tungsten skeleton fusion infiltration, activation sintering, high-temperature liquid-phase sintering, vacuum sintering, and injection molding sintering. The microstructures of CuW composites produced under different process conditions are very different, and their comprehensive properties are therefore significantly different [4][5][6][7].…”
Section: Preparation Process Of Cuw/graphene-enhanced Cuw Composites ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Existing processes for the preparation of copper-based contact materials include: induced copper powder fusion infiltration, pre-sintered tungsten skeleton fusion infiltration, activation sintering, high-temperature liquid-phase sintering, vacuum sintering, and injection molding sintering. The microstructures of CuW composites produced under different process conditions are very different, and their comprehensive properties are therefore significantly different [4][5][6][7].…”
Section: Preparation Process Of Cuw/graphene-enhanced Cuw Composites ...mentioning
confidence: 99%
“…Copper-tungsten (CuW) composites, as a prototypical two-phase pseudo-alloy, integrate the high conductivity and thermal conductivity of copper with the exceptional strength and arc ablation resistance of tungsten. Owing to these advantageous characteristics, CuW composites, especially CuW80 (80 wt.% W content), are extensively utilized as electrical contacts in high-voltage circuit breakers [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…So, it is seen that the number of black gaps in the contact runners given in Figures 7 and 8 has decreased. The low wear resistance of some CuW pins exposed to high temperatures is explained by the lower high temperature wear resistance and arc ablation resistance of CuW composites produced with standard powder metallurgy, resulting in different wear resistances (Zou et al, 2020). As seen in Figure 6a, it has been determined that the contact tips were welded to the main terminal body, and it is thought that the pin tips, which reach very high temperatures during the test phase, will be joined in this way both due to the high current effect and also due to the high ambient temperature.…”
Section: Microscopic Studymentioning
confidence: 99%
“…In addition, severe wear occurs due to sliding contact at high loads and high speeds. In both aluminum alloys and Al2O3/Al alloy composites, the occurrence of severe wear is also affected by normal load, sliding speed, and sliding distance, and is characterized by significant increase in wear rate, large surface wear, and even large-scale material transfer to the counter surface (Deuis et al, 1997;Zou et al, 2020;Childs, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…German concluded that bimodal powder mixtures can improve the green density of powder systems and are used in the process such as slip casting and powder injection molding [ 18 ]. Zou et al reported that W–30Cu composite prepared by grading W powder has a homogenous microstructure and higher hardness and electrical conductivity [ 19 ]. However, the raw material used in this research was commercial W powder, which has a wide particle size distribution and a large number of agglomerated particles.…”
Section: Introductionmentioning
confidence: 99%